2021
DOI: 10.31234/osf.io/s276e
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reducing Anhedonia in Major Depressive Disorder with Future Event Specificity Training (FEST): A Randomized Controlled Trial

Abstract: Objective: Improving future thinking may be one means to reduce anhedonia, particularly in Major Depressive Disorder (MDD) in which future thinking is impaired. The current study therefore examined whether enhancing future thinking is a viable method of reducing anhedonia in MDD. Methods: Participants (N=177; 80.8% women; M age=43.7, SD=11.8) with a current depressive episode including anhedonia and high symptom severity were randomized to a Future Event Specificity Training (FEST) program or wait-list control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…An e-PASS diagnosis corresponds well with the Mini-International Neuropsychiatric Interview (MINI; Sheehan et al, 1998;Nguyen et al, 2015). Specifically, a concordance of 96.2% has been found among adults (Hallford et al, 2021b) and a concordance of 91.9% among youth (Hallford et al 2021a).…”
Section: Diagnosismentioning
confidence: 86%
“…An e-PASS diagnosis corresponds well with the Mini-International Neuropsychiatric Interview (MINI; Sheehan et al, 1998;Nguyen et al, 2015). Specifically, a concordance of 96.2% has been found among adults (Hallford et al, 2021b) and a concordance of 91.9% among youth (Hallford et al 2021a).…”
Section: Diagnosismentioning
confidence: 86%
“…In particular, focusing on spatial details might be one method through which to increase anticipated pleasure (the expectation of enjoyment) and anticipatory pleasure (the feeling of pleasure from preexperiencing) for positive events, the perceived control we have over them, and our behavioural intentions. Previous research has indicated that detail and vividness is correlated with more use of mental imagery (Hallford et al, 2020b), and that both detail and vividness and mental imagery are related to higher anticipatory and anticipated pleasure (Hallford et al 2020a), a stronger sense of perceived control (Jing et al, 2016) Trials in clinical groups (Hallford et al, 2020c(Hallford et al, , 2021 and non-clinical groups (Hallford et al, 2020d) have already shown that training in enhancing the ability to produce detail and specificity in future thinking can influence such processes. Distinguishing the effects of particular types of details would provide a more nuanced understanding of their benefit in functioning.…”
Section: Introductionmentioning
confidence: 99%